Tolstoy and Tolstaya : A Portrait of a Life in Letters - Tolstai︠a︡, S. A. (Sofʹi︠a︡ Andreevna), 1844-1919; Tolstoy, Leo, 1828-1910; Gladkova, Liudmila, 1954-; Klioutchanski, Arkadi, 1965-; Woodsworth, John, 1944-; Donskov, Andrew, 1939- (Book collections on Project MUSE., 2017)
Tolstoy and Tolstaya's legacy is still regarded as one of the greatest contributions to Russian history and world literature, while their daily life has been recorded through their correspondence. This work presents the last 239 letters plus 11 hitherto unpublished letters between the spouses, painting a remarkable portrait of their life and times.